Evaluation of Colour Stability of Activa Pronto and Beautifil Flow Plus in Three Different Solutions - An In Vitro Study - Venkadessan, Kalaivani; L, Leelavathi; Indiran, Meignana Arumugham (South Eastern European Journal of Public Health, 2024)
Objective: To assess the colour stability of two bioactive restorative materials Activa Pronto (Pulpdent, USA) and Beautifil Flow Plus (Shofu, Japan) when exposed to three commonly consumed beverages: coffee, tea, and Coca-Cola. Materials and Methods: 80 disc-shaped specimens were prepared, 40 samples each of the material and were divided into four groups based on the staining solution, which included: distilled water (control), coffee, tea, and Coca-Cola. The specimens were placed in the respective solution for 30 days. Solutions were replaced daily to avoid contamination. Color measurements were performed before (baseline) and after 30 days using a VITA Easyshade spectrophotometer, and the colour changes (ΔE) were calculated in the CIE Lab* system. Results: For the ΔE values, Activa Pronto showed significantly lower values than Beautifil Flow Plus in both coffee (p=0.001) and Coca-Cola (p=0.000) solutions. In the tea group, no significant difference was observed (p=0.223). Activa Pronto generally had more stable color, especially in acidic and staining solutions like coffee and Coca-Cola solutions. Conclusion: Activa Pronto presented greater color stability than Beautifil Flow Plus; therefore, it is a more suitable material for patients who would take much notice of the aesthetic appearances of their restorations in the long term. The most stained materials by Coca-Cola and coffee meant further investigation into the long-term clinical behaviour of these materials was essential.